A blueprint for vitamin D fortification in sugar: stability and health impact - Hardinsyah, Hardinsyah; Rahmawati, Rahmawati; Sulaeman, Ahmad; Nurkolis, Fahrul (Frontiers in Nutrition, 2025)
Vitamin D deficiency is a global health concern, and fortifying widely consumed staples offers a scalable solution. Granulated sugar, accessible across socio-economic groups, shows promise as a novel vehicle for cholecalciferol delivery. Evidence indicates that vitamin D3 stability can be maintained through encapsulation and protective packaging, with over 90% potency retained under proper storage. Fortified sugar demonstrates good bioavailability, achieving absorption comparable to dairy products, and could increase serum 25(OH)D by 10–20 nmol/L at the population level. While offering low-cost impact, fortification requires careful dosing, quality control, and public education to mitigate risks of hypervitaminosis and prevent misperceptions that sugar itself is a health food.